BUKU ILUSTRASI WAYANG TIMPLONG SEBAGAI MEDIA PENGENALAN BUDAYA NGANJUK UNTUK ANAK-ANAK - Fika Khoirun Nisa (AMARASI: JURNAL DESAIN KOMUNIKASI VISUAL, 2025)
to the lack of interest among younger generations. Introducing Wayang Timplong to children has become a strategic step in preserving this cultural heritage, one method being through a simple comic-based illustrated book. Observations and interviews revealed a shortage of innovative and engaging educational media about Wayang Timplong for children. The design of the illustrated book titled Wayang Timplong uses a mixed research method, consisting of two stages: the preparation stage and the creation stage. The preparation stage includes data collection, 5W+1H analysis, and synthesis. Meanwhile, the creation stage involves pre-production, production, and post-production. Through an interactive visual approach, it is hoped that children will not only become familiar with but also grow to love and take pride in this traditional art form. The research findings show that introducing the Wayang Timplong culture through creative media can enhance children's understanding of local cultural traditions and support efforts to preserve them in the future.